INVESTIGATING PERCEPTION OF WORK-LIFE BALANCE AMONG WOMEN TEACHERS; AN EXPLORATORY STUDY - Nimya M P; V. Senthilkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Work-life balance has emerged as a critical consideration in contemporary workplaces across various professions, including teaching. In the educational sector, where demands can be relentless and expectations high, achieving a balance between professional responsibilities and personal life is crucial. The article delves into the intricate relationship between work-life balance and teacher job satisfaction, highlighting work and personal life significantly impacts educators' overall contentment and effectiveness. Teaching is often perceived as more than just a job; it's a vocation. However, the inherent passion for educating should not overshadow the necessity of maintaining a healthy work-life balance. Teachers frequently find themselves immersed in a multitude of tasks beyond classroom instruction, including lesson planning, grading, and extracurricular activities. The demands of the profession can lead to extended working hours, encroaching upon personal time and potentially causing burnout. Educational institutions can support teachers in enhancing their self-efficacy by promoting strategies that foster a healthy work-life balance. Providing professional development opportunities focused on time management, stress reduction, and self-care can empower educators to develop the skills and confidence needed to maintain balance in their lives. Creating a supportive work environment that values work-life balance and offers resources for managing workload and stress.